Perlindungan Hukum terhadap Korban Kekerasan Seksual Berbasis Digital oleh Mantan Pasangan (Revenge Porn) - Vierdan Adha Putra Harjanto; Simon Nahak; I B GD Agustya Mahaputra (CV WAHANA PUBLIKASI, 2026)
The rapid development of information and communication technology has transformed social interactions while simultaneously creating new forms of crime, including digital-based sexual violence. One of the most prevalent forms is revenge porn, namely the dissemination or threat to disseminate intimate images or videos without the victim’s consent, resulting in violations of privacy, dignity, sexual autonomy, and psychological well-being. This study aims to analyze the legal framework governing revenge porn in Indonesia and examine the criminal law protection provided to victims. The research employs a normative legal method using statutory and conceptual approaches, with legal materials collected through library research and analyzed using legal interpretation. The findings indicate that revenge porn is not regulated under a single, specific legal instrument; instead, its legal basis is dispersed across the Criminal Code, Law Number 1 of 2024 concerning Electronic Information and Transactions, Law Number 44 of 2008 concerning Pornography, and, most importantly, Law Number 12 of 2022 concerning Sexual Violence Crimes, particularly Article 14 on electronic-based sexual violence. Criminal law protection extends beyond the prosecution and punishment of offenders to include victim-oriented measures such as identity protection, legal assistance, psychological and social recovery, and the right to restitution. Nevertheless, the implementation of these protections remains constrained by overlapping legal provisions, limited understanding among law enforcement officials regarding the characteristics of digital sexual violence, difficulties in controlling the circulation of digital content, and persistent social stigma against victims. Therefore, stronger regulatory harmonization, improved law enforcement capacity, effective digital content removal mechanisms, and enhanced public legal awareness are essential to ensure comprehensive, victim-centered protection against revenge porn.